Development and Psychometric Evaluation of the Nursing Instructors’ Clinical Teaching Performance Inventory - Farahani, Mansoureh A. (Glob J Health Sci, 2015)
Evaluation of nursing instructors’ clinical teaching performance is a prerequisite to the quality assurance of nursing education. One of the most common procedures for this purpose is using student evaluations. This study was to develop and evaluate the psychometric properties of Nursing Instructors’ Clinical Teaching Performance Inventory (NICTPI). The primary items of the inventory were generated by reviewing the published literature and the existing questionnaires as well as consulting with the members of the Faculties Evaluation Committee of the study setting. Psychometric properties were assessed by calculating its content validity ratio and index, and test-retest correlation coefficient as well as conducting an exploratory factor analysis and an internal consistency assessment. The content validity ratios and indices of the items were respectively higher than 0.85 and 0.79. The final version of the inventory consisted of 25 items, and in the exploratory factor analysis, items were loaded on three factors which jointly accounting for 72.85% of the total variance. The test-retest correlation coefficient and the Cronbach’s alpha of the inventory were 0.93 and 0.973, respectively. The results revealed that the developed inventory is an appropriate, valid, and reliable instrument for evaluating nursing instructors’ clinical teaching performance.